Plant-inspired adhesive and tough hydrogel based on Ag-Lignin nanoparticles-triggered dynamic redox catechol chemistry - Donglin Gan (Nature Portfolio, 2019)
Biomimetic catechol-based adhesives have attracted significant interest but can lose adhesion due to excessive oxidation. Here, the authors report on the addition of silver-Lignin nanoparticles as a dynamic catechol redox system to maintain catechol/quinone balance, making a reusable, antibacterial bioadhesive.